Assessment of the factors affecting the loss of workforce in patients with traumatic hand injury - ŞANAL TOPRAK, CANAN (My University, 2022)
Objective: This study aimed to examine the factors affecting the loss of workforce, including the time to return to work and workrelated situations in patients with traumatic hand injury who were taken to a hand rehabilitation program.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Hand injury; Modified Hand Injury Severity Score; Return to work; workplace engagement; WORK OUTCOMES; SEVERITY; RETURN; IMPAIRMENT